Qualitative Analysis of Public Perception of Work Ethics in Nigeria’s Public Sector - Afolayan, Michael Ayorinde; Aderibigbe, Adefisayo Ebenezer; Okanlawon, Tobiloba (Unisia, 2023)
The Nigerian public service is crucial to the country’s economic development. This is because a vibrant public service sector is able to harness effectively overhead taxes and also account for public expenditure at all levels. In this study, we qualitatively analyse the response of 15 individuals from the public who have visited a typical public office at least 3 times within the last one year. An interview form containing 7 items was administered, and the results was analyzed from themes that give true picture of the perception of respondents. It was observed that workers in public service are not professional enough, taking their jobs with levity. The level of unprofessionalism in the public workforce calls for urgent attention as the study finds. Public service workers make up the larger part of the workforce of the nation, and as such they represent the face of the nation to the committee of nations. Government at all levels, that is the federal, the state, and the local council level as well as the various government agencies, departments, and ministries are called upon to cooperate and synergize in order to foster rapid transformation in public service. As a result, this study recommends publics service reforms.